The influence of the guided discovery learning model on critical thinking abilities and scientific attitudes - Rima Nur Iman; Nurrohmatul Amaliyah; Tri Isti Hartini (ARKA INSTITUTE, 2024)
This research aims to examine improving students' critical thinking skills and scientific attitudes using the Guided Discovery Learning learning model. Critical thinking and scientific attitudes are important aspects to develop in learning, especially in science learning in elementary schools. Critical thinking is part of the cognitive work process and a scientific attitude develops affective aspects. A quasi-experimental study using a pretest-posttest control group design is the research methodology. Students in the fifth grade at SDN Bukit Duri 05 in South Jakarta served as the research subjects. The control group received therapy using the Free Discovery Learning learning model, whereas the experimental group received treatment using the Guided Discovery Learning learning model. According to the study's findings, there was no difference between the experimental class's and the control group's early critical thinking skills. The results showed that there was no difference between the experimental class and the control class in terms of early scientific attitude abilities. Additionally, compared to students in the control class, those in the experimental class showed a different growth in critical thinking abilities. Lastly, it was discovered that the experimental class and the control class had different rising scientific views.